Preferred Crystallographic Orientation via Solution Bathing for High‐Performance Inverted Perovskite Photovoltaics - Zhang, Xinyue; Shang, Chuanzhen; Wang, Chenyun; Zhao, Wenying; Tao, Cong; Wang, Shasha; Zhang, Xuewen; Han, Ruilin; Zhou, Bin; Qu, Duo; Wang, Shibo; Wang, Ying; et al. (Advanced functional materials, 2024)
The meticulous control of crystal facets in polycrystalline perovskite films offers valuable insights into the photoelectric properties, varying significantly with different orientations. Exploring effective means to regulate these facets is crucial, and further revealing the underlying mechanisms is needed. Here, the research employed green solution bathing to obtain high‐quality perovskite films with preferred crystallographic orientation. In brief, eco‐friendly 2‐pentanol is used as the solvent, and functional molecules 2‐(dimethylaminomethyl)‐4‐(2‐aminoethylthiomethyl)thiazole (DAT) are introduced into the solution bathing as the solute. By introducing DAT molecules, precise control over perovskite crystal nucleation kinetics is achieved, resulting in films with a preferential (100) facet orientation. Conversely, films without DAT exhibited distinct (111) facet orientation. The regulation of DAT on perovskite film crystal facet is verified through theoretical and crystallographic analyses. Theoretical calculations show that S atom of DAT binds most strongly to the (100) facet of FAPbI3, promoting surface energy reduction and thermodynamic enhancement, favoring (100) crystal orientation. Crystallographic characterization further proved the regulation effect. In addition, PL/TRPL tests confirm the regulation of DAT on superior photoelectric properties of (100)‐oriented perovskite films. The work introduces a novel approach and preparation process for regulating the crystal facets orientation of polycrystalline perovskite films. Control of crystal facet in polycrystalline perovskite films offers valuable insights into the photoelectric properties. This work explores effective means to regulate facets and further reveals the mechanisms based on solution bathing. By introducing (dimethylaminomethyl)−4‐(2‐aminoethylthiomethyl)thiazole (DAT) molecules into solution bathing as solute, the orientation of the perovskite film from a (111) facet to a preferred (100) crystal facet is implemented.